(untitled) (BRAC University Journal, 2026)
Over the past few years, there has been a revival of interest in the English language in Bangladesh with the government putting a lot of emphasis on the teaching and learning of English. There have been a plethora of initiatives at the macro-level to strengthen English language education in urban as well as rural areas in the country which are to a certain extent complemented by micro-level initiatives at the family level. Parents aspire for their children to master the English language and spend on private tuition according to their abilities to ensure that learners achieve good results in English and other subjects. Young people, on their part, are keen to learn and use English alongside Bangla, sometimes mixing them together in the same breath in ways that appear outrageous and ridiculous to a lot of people holding tenaciously onto rather conservative views about roles and use of language in national identity formation. Although there is a general consensus that Bangladeshis need English to move ahead in the context of globalization, how English should be used, where and to what extent are issues that are far from being resolved. English is viewed both as an essential lingua franca and a threat to the vitality of Bangla. English is also often blamed for the perceived corruption of Bangla in the media. This paper focuses on the ambiguities and tensions surrounding the roles and use of English vis-à-vis Bangla in Bangladesh.